Peran Modal Intelektual Keunggulan Kompetitif Dan Kemampuan Inovasi Terhadap Kinerja Usaha Kecil Menengah Kabupaten Badung Bali - Merta I Ketut; Sekariani Ni Nyoman; Yusnimi Ni Made (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research takes the object of Small and Medium Enterprises in Badung Regency, Bali. The aim is to test the Role of Intellectual Capital, Competitive Advantage and Innovation Ability on the Performance of Small and Medium Enterprises using grand theory.Stewardship (Davis et al, 1997).Quantitative Multiple Regression Research Method with a sample of 63 and data analysis using SPSS Version 24.Research Results (1) Innovation Capability has a Negative and insignificant effect on the Performance of Small and Medium Enterprises, (2) Competitive Capability Intellectual Capital has a positive and significant impact on Small Business Performance, (3) Innovation Capability has a Positive and significant impact on Competitive Capability Intellectual Capital , (4) Intellectual Capital, Competitive Ability, has not been able to mediate Innovation Ability on the Performance of Small and Medium Enterprises in Badung Regency, Bali.Implications of this research found that the influence on the performance of small and medium enterprises in Badung Regency was moderate, and Intellectual Capital, Competitive Ability and Innovation Ability were found to be partially unable to improve performance directly or indirectly.